Vaccine-induced pityriasis rosea and pityriasis rosea-like Eruptions: A review of literature and a case report of COVID-19 vaccine-induced pityriasis rosea - Eman Almukhadeb; Faisal A Alghubaywi; Yousef Alharthi; Amer Alharbi (Wolters Kluwer Medknow Publications, 2022)
Pityriasis rosea (PR) is frequently proposed to result from a viral etiology. In line with the current pandemic, COVID-19 vaccines are noticed to trigger PR development. Our patient is a 23-year-old female who developed an itchy skin rash following the Pfizer-BioNTech COVID-19 vaccine. Examination showed one erythematous plaque on the left shoulder and multiple small scaly plaques of similar appearance distributed over the trunk and proximal extremities. The patient was clinically diagnosed, educated, reassured, prescribed topical mometasone ointment and oral chlorpheniramine, and was given a follow-up appointment. We report this case to increase awareness on COVID-19 vaccines as potential triggers of PR.